Teaching local history with the use of De Bonoâ€™s Six Thinking Hats, brainstorming; and role play in primary school, multicultural classes- an example of application in Greek school - Despoina Kapsali (Universitas Majalengka, 2023)
Î¤his study presents an example of an intercultural teaching practice of cultivating of critical thinking and intercultural/ historical literacy in the context of local history learning. The practice was created by the author in the framework of the European eTwinning project â€œThe young time travelers of historyâ€ (which was awarded with the Greek National Quality Label and the European one) and was presented as an example of good practice in teacher seminars at the local level. This practice combines a simplified form of De Bonoâ€™s Six Thinking Hats with role-playing and brainstorming and emerged from the study of the social-historical background of a primary school multicultural class in which was implemented. Finally, this specific study aims to be an example for the creation of other innovative, alternative teaching practices in local history learning.